La série Barbapapa: artisanat soixante-huitard ou stratégie marketing bien rodée ? - Cécile Boulaire (Strenae)
The Barbapapa series, born in 1970, is often presented as the result of an unexpected creative impulse, born in a Franco-American couple and stimulated by the context of Parisian life. It can also be seen from another angle: that of a dazzling commercial success, due to multi-media and international strategies that leave nothing to chance. This article will explore the two sides of this editorial adventure.